Research and implementation of network transmission situation awareness - ZHUO Ying; GONG Chun-ye; GONG Zheng-hu (Tongxin xuebao)
The advanced ideas of situation awareness were introduced to network transmission and NTSA（network transmission situation awareness） model was established based on spatial traffic clustering.Around the key technologies of the model,situation factors were selected according to information gain and mutual information;a high-dimensional data stream clustering algorithm for transmission pattern partition as well as a topology importance analysis method of network element based on graph theory were proposed;furthermore,a NTSA prototype system was designed and imple-mented.The experiment results on real datasets demonstrate the efficiency,effectiveness and scalability.